Managing the defiant child a guide to parent training - Barkley, Russell A., 1949-; Guilford Publications, Inc. (New York, N.Y. : Guilford Publications, Inc., 1997)
Childhood defiance --the most common complaint of parents seeking professional help for their children --exerts a tremendous amount of wear-and-tear on families. This video brings a proven approach to behavior management, and shows clinicians, school practioners, parents, students, and teachers how enhanced parenting skills can improve the parent-child relationship.
Title from cassette label.
Keywords: Child rearing; Parenting; Oppositional defiant disorder in children